PENGAMANAN DATABASE MENGGUNAKAN MODEL HIBRID BLOCKCHAIN DAN HOMOMORPIC ENCRYPTION DENGAN OPTIMASI ZERO-KNOWLEDGE PROOF - Muhammad Muzammil; Deden Pratyaten; Nadia Cahaya Islami; Kartika Imam Santoso; Eko Supriyadi (LPPM Universitas An Nuur, 2026)
Database security has become a crucial issue with the increasing cyber threats and data breaches that significantly impact organizations and individuals. This research proposes an innovative hybrid model that integrates blockchain technology, homomorphic encryption, and zero-knowledge proof to secure databases. This approach offers a multi-layer security mechanism that enables user identity verification without exposing credentials, encrypted data processing, and immutable access tracking. The research method uses an experimental approach with attack simulations on databases implemented with and without the proposed hybrid model. Results show significant improvements in resistance against SQL injection attacks (99.7%), man-in-the-middle attacks (98.2%), and unauthorized access (100%) compared to conventional methods. Although there is a trade-off in the form of a 12% latency increase, this hybrid model offers an optimal balance between security and performance. The main contribution of this research is the development of zero-knowledge proof integration algorithm that optimizes the verification process by reducing computational overhead by 35% compared to conventional implementations.